Individual and context-evoked antecedents of exploration-exploitation performance - Richner, Jan; Zagorac-Uremović, Zorica; Laureiro-Martínez, Daniella (Frontiers in Psychology, 2023)
A central issue within the Carnegie approach is the exploration–exploitation tension that lies behind organizational adaptation. After decades of research, there is still little understanding how the combination of individual and context-evoked differences affects exploration-exploitation performance. To address this issue, we build on recent psychological and neuroscientific studies to develop and test an integrative model. The model considers individual antecedents as personality and cognitive flexibility, and context-evoked antecedents that capture the effect of task-unrelated context (i.e., recent stress and present emotional states) that take place along different time horizons and aspects of the more immediate task context (i.e., task motivation). We rely on a lab-in-the-field study of 282 leaders within the Swiss Armed Forces—an organization that exhibits the exploration–exploitation tension in an accentuated form. We employ a structural equation model with a multiple-mediation path analysis, aimed at testing complex interactions between multiple variables. Our findings highlight the need to take an integrative approach; cognitive flexibility mediates the positive effect of the personality trait of emotional stability on exploration-exploitation performance, however both cognitive flexibility and emotional stability play unique, underlying roles in explaining how organizational leaders interpret the context. Emotional stability decreases the negative effect of recent situational stress on a leader’s cognitive flexibility. Cognitive flexibility, in turn, mediates the effect of the present positive affective signals of task motivation on exploration-exploitation performance. These findings shed new light on our understanding of how adaptive leaders leverage positive and negative context-evoked antecedents that, in turn, affect cognitive flexibility and exploration-exploitation.